1999
DOI: 10.1111/j.1600-065x.1999.tb01399.x
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of the major histocompatibility complex: haplotypes, duplication, retroviruses and disease

Abstract: The genomic region encompassing the Major Histocompatibility Complex (MHC) contains polymorphic frozen blocks which have developed by local imperfect sequential duplication associated with insertion and deletion (indels). In the alpha block surrounding HLA-A, there are ten duplication units or beads on the 62.1 ancestral haplotype. Each bead contains or contained sequences representing Class I, PERB11 (MHC Class I chain related (MIC) and human endogenous retrovirus (HERV) 16. Here we consider explanations for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
351
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(366 citation statements)
references
References 153 publications
12
351
1
2
Order By: Relevance
“…This is especially so in the region extending from HLA-B to HLA-DR, where haplotypes seem to have been conserved from remote ancestors and have been called conserved, extended, or ancestral haplotypes. It has been estimated that ϳ70% of the human haplotypes are conserved, extended haplotypes or recombinants of no more than two of them (17,32,33). It is generally accepted that a small number of these MHC conserved haplotypes are found in the majority of IgAD patients (5,7,8,10,11,13,19) and that these haplotypes share a susceptibility locus designated IGAD1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially so in the region extending from HLA-B to HLA-DR, where haplotypes seem to have been conserved from remote ancestors and have been called conserved, extended, or ancestral haplotypes. It has been estimated that ϳ70% of the human haplotypes are conserved, extended haplotypes or recombinants of no more than two of them (17,32,33). It is generally accepted that a small number of these MHC conserved haplotypes are found in the majority of IgAD patients (5,7,8,10,11,13,19) and that these haplotypes share a susceptibility locus designated IGAD1.…”
Section: Discussionmentioning
confidence: 99%
“…Some early studies already signaled that the association was with particular combinations of MHC alleles rather than with individual alleles per se (5,7) and that these combinations reflected extended, conserved, or "ancestral" haplotypes A1-B8-DR3, A28-B14-DR1, and B44-DR7 (7,8,11,15). The conservation of these haplotypes, which appear derived from a common remote ancestor (16,17), has rendered difficult the identification of the individual genes responsible for IgAD.…”
mentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24] Besides, it usually occurs on the ancestral haplotype 7.1. 4,12,20,25 Thus, it has been suggested that an estimated 60 to 70 generations ago, this mutation occurred in the HFE gene of a Celtic individual who is the ancestor of more than 5% of white subjects now carrying the allele. 4,26 In contrast, the H63D substitution is not restricted to European populations, being found at allele frequencies of more than 5% in countries bordering the Mediterranean, in the Middle East, and in the Indian subcontinent, suggesting that the H63D substitution must have occurred earlier than the C282Y substitution.…”
Section: Correspondence: Prof C Caruso Laboratorio Di Immunopatologmentioning
confidence: 99%
“…12,13 As is the case for most autoimmune diseases, MG has a complex genetic control. 14 The extended HLA-A1-B8-DR3 haloptype, also called the 8.1 ancestral haplotype, 15 has long been associated with the form of MG with thymus hyperplasia, 16 defining the MYAS1 locus. 17 Association with HLA, however, explains the genetic component of MG only partly.…”
Section: Introductionmentioning
confidence: 99%